Multicenter prospective evaluation of an overtube endoluminal interventional platform for colorectal polypectomy - Othman, Mohamed O.; Diehl, David L.; Khara, Harshit S.; Jawaid, Salman; Yang, Dennis; Draganov, Peter V. (Endoscopy International Open, 2023)
Background and study aims Endoscopic removal of complex colorectal polyps (≥ 2 cm) can be technically challenging. A dual balloon endoluminal overtube platform (DBEP) was developed to facilitate colonoscopic polypectomy. The study purpose was to evaluate clinical outcomes with the DBEP for complex polypectomy.Patients and methods This was an observational, prospective, multicenter Institutional Review Board-approved study. Between January 2018 and December 2020, safety and performance data were collected intra-procedurally and at 1 month post-procedure in patients undergoing intervention with the DBEP at three US centers. The primary endpoint was device safety and technical success of the procedure. Secondary endpoints included navigation time, total procedure time, and user feedback assessment post-procedure.Results A total of 162 patients underwent colonoscopy with the DBEP. Of these, 144 (89 %) underwent 156 interventions successfully with DBEP (44.5 % endoscopic mucosal resection, 53.2 % hybrid endoscopic submucosal dissection (ESD)/ESD, 1.3 % other). In 13 patients (8 %), device challenges contributed to unsuccessful intervention. One mild device-related adverse event (AE) occurred. Procedural AE rate was 8.3 %. Median lesion size was 2.6 cm [range 0.5–12]. The investigators felt that navigating the device was easy/somewhat easy in 78.5 % of successful cases. Median total procedure time was 69 minutes [range, 19–213], median navigation time to lesion was 8 minutes [range, 1–80], And median polypectomy time was 33.5 minutes [range, 2–143].Conclusions Endoscopic colon polyp resection with the DBEP was safe with a high technical success rate. The DBEP has the potential to provide enhanced scope stability and visualization, traction, and a conduit for scope exchange. Further prospective randomized studies are warranted.